Assessing the quality of administrative data for research: a framework from the Manitoba Centre for Health Policy. (1st September 2017) - Smith, Mark; Lix, Lisa M; Azimaee, Mahmoud; Enns, Jennifer E; Orr, Justine; Hong, Say; Roos, Leslie L
Abstract: The growth of administrative data repositories worldwide has spurred the development and application of data quality frameworks to ensure that research analyses based on these data can be used to draw meaningful conclusions. However, the research literature on administrative data quality is sparse, and there is little consensus regarding which dimensions of data quality should be measured. Here we present the core dimensions of the data quality framework developed at the Manitoba Centre for Health Policy, a world leader in the use of administrative data for research purposes, and provide examples and context for the application of these dimensions to conducting data quality evaluations. In sharing this framework, our ultimate aim is to promote best practices in rigorous data quality assessment among users of administrative data for research.